Hak Cuti Haid Tenaga Kerja Perspektif Maślaĥah Al-Mursalah dan Gender - Muhammad Julijanto; Devi Andrianti (Az-Zahra, 2022)
This article discusses the right to menstrual leave as stated in Article 81 of Law No. 13 of 2003 on Employment in PT Jaya Asri Garmin do. This research data was obtained through interviews with relevant parties, namely personnel, and the female workforce, observation, and documentation. This research uses theories about the understanding of labor in general, labor rights according to Law No. 13 of 2003 on Employment, Gender Concepts and Analysis, menstrual understanding, and also contains theories about Maŝlaĥah Al-Mursalah. This study found that menstrual leave rights as in Law No. 13 of 2003 on Employment have been applied at PT Inti Sukses Garmindo but replaced with money or cashed. The award of bonus to replace menstrual leave amounted to Rp 89,195, - which will be received every month. But it is not by Law No. 13 of 2003 on Employment that should replace the cashed menstrual leave rights 2 x 89,195, - every month. The application of menstrual leave rights in Law No. 13 of 2003 on Employment at PT Inti Sukses Garmindo if reviewed with Maŝlaĥah Al-Mursalah then includes maintaining the soul. If analyzed using Gender Analysis APKM (Access, Participation, Control, Benefits). With the provision of menstrual leave, it can protect against the exploitation of women because menstruating women often feel pain, dizziness, and weakness. The provision of menstrual leave can be used as a time of rest and avoid evil.